2020
DOI: 10.1002/adma.201907289
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated Mesoporous 2D Covalent Organic Frameworks for High‐Rate Electrochemical Double‐Layer Capacitors

Abstract: The electrochemical double‐layer capacitors (EDLCs) are highly demanded electrical energy storage devices due to their high power density with thousands of cycle life compared with pseudocapacitors and batteries. Herein, a series of capacitor cells composed of exfoliated mesoporous 2D covalent organic frameworks (e‐COFs) that are able to perform excellent double‐layer charge storage is reported. The selected mesoporous 2D COFs possess eclipsed AA layer‐stacking mode with 3.4 nm square‐like open channels, favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 51 publications
4
122
0
Order By: Relevance
“…4f). In the Nyquist plots, the straight line at the low-frequencies reveals convenient ion transport path, while the small semicircle at the high-frequencies indicates very low internal electrode-electrolyte resistance and efficient charge mobility in the capacitor device 9 . Therefore, it can be concluded that the 3D structure of COF/rGO material is beneficial for the rapid charge transfer and ion diffusion to redox-active sites, providing guarantee for the outstanding electrochemical performance of the supercapacitor.…”
Section: Resultsmentioning
confidence: 99%
“…4f). In the Nyquist plots, the straight line at the low-frequencies reveals convenient ion transport path, while the small semicircle at the high-frequencies indicates very low internal electrode-electrolyte resistance and efficient charge mobility in the capacitor device 9 . Therefore, it can be concluded that the 3D structure of COF/rGO material is beneficial for the rapid charge transfer and ion diffusion to redox-active sites, providing guarantee for the outstanding electrochemical performance of the supercapacitor.…”
Section: Resultsmentioning
confidence: 99%
“…C) Ragone plot, presenting a comparison between current work (black circles) and devices comprising vertically aligned CNTs (blue circles), [10] MoSe 2 (red triangulars), [46] MXene/polymer (green diamonds), [27] and covalent organic framework (brown squares). [15] excellent capacitor behavior, accounting for the linear respond of the voltage and the low IR-drop (0.06 V at 200 mA cm À 2 ), even in current densities up to 2000 mA cm À 2 , which is among the highest areal current densities reported for such thin layers. [10,15,27,46] This areal current density also corresponds to a high volumetric current density of more than 300 A cm À 3 for the entire device, including the current collector and spacer, which is significantly higher than commercial capacitors.…”
Section: Electrochemical Properties Of a Symmetric Niru/ruo 2 Supercamentioning
confidence: 89%
“…[15] excellent capacitor behavior, accounting for the linear respond of the voltage and the low IR-drop (0.06 V at 200 mA cm À 2 ), even in current densities up to 2000 mA cm À 2 , which is among the highest areal current densities reported for such thin layers. [10,15,27,46] This areal current density also corresponds to a high volumetric current density of more than 300 A cm À 3 for the entire device, including the current collector and spacer, which is significantly higher than commercial capacitors. Indeed, considering that the thickness of the active layer is less than 2 % of the overall volume of the device, the volumetric current density may be easily further increased upon reducing the thickness of the Ni current collector (currently 20 μm).…”
Section: Electrochemical Properties Of a Symmetric Niru/ruo 2 Supercamentioning
confidence: 89%
See 1 more Smart Citation
“…151 Some examples for the preparation of NCOFs by ultrasonic exfoliation are shown in Table 2. [150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165] Evidently, the weaker the interactions between the COF layers, the easier it becomes to perform ultrasonic exfoliation. TPA-COF constructed with tris(4-aminophenyl)amine and tris(4-formylphenyl)amine exible monomers with the C 3v symmetry conrmed this prediction.…”
Section: Nanocrystallization Of Cofsmentioning
confidence: 99%